Optimizing Pain Management in Truncal Surgery: A Narrative Review of Regional Anesthetic Techniques - Małek, Dominik; Jurczak, Paweł; Sztaba, Klaudia; Puczel, Paweł Karol; Siwek, Marta (Journal of Education, Health and Sport, 2025)
Background. Effective postoperative analgesia is essential for optimizing recovery and enhancing patient satisfaction after surgery. Regional anesthesia techniques, particularly fascial plane blocks, are key components of multimodal analgesia, offering targeted somatic and sometimes visceral pain relief. Aim. To review the indications, techniques, efficacy, contraindications, and complications of commonly used truncal regional anesthesia blocks, including TAP, subcostal TAP, quadratus lumborum, rectus sheath, ilioinguinal/iliohypogastric, intercostal, PECS I & II, and serratus anterior plane blocks. Material and methods. A narrative review of recent clinical studies and systematic reviews was performed, focusing on ultrasound-guided fascial plane blocks in abdominal, thoracic, and breast surgeries. Data on efficacy, safety, and clinical application were synthesized to guide perioperative analgesic strategies. Results. TAP and subcostal TAP blocks effectively reduce somatic pain after lower and upper abdominal surgery, respectively, while quadratus lumborum blocks provide both somatic and visceral analgesia. Rectus sheath and ilioinguinal/iliohypogastric blocks are effective for midline and lower abdominal procedures. Intercostal, PECS, and serratus anterior plane blocks offer targeted analgesia for thoracic and breast surgery. Ultrasound guidance enhances safety and efficacy. Complications are rare and include local anesthetic toxicity, bleeding, infection, or block failure, with specific risks such as pneumothorax (ICNB) or transient femoral nerve palsy (TAP, ilioinguinal/iliohypogastric). Conclusions. Truncal regional anesthesia techniques play a vital role in multimodal analgesia, improving pain control, reducing opioid use, and supporting enhanced recovery after surgery. Optimal block selection should be tailored to the surgical site and patient factors. Further high-quality studies are needed to refine techniques and optimize outcomes.